Soil protection in sloping mediterranean agri-environments: lectures and exercises - Evelpidou, Niki (2009)
The long history of the Mediterranean records striking examples of success and failure of land use models and management practices, which, in the latter case, are a heavy heritage for the soil resource in this basin. At present day, many forms of soil degradation threaten Mediterranean soils as, for instance, salinization, pollution, structural degradation and erosion. There is a geographical pattern of distribution of these forms of soil degradation and soil erosion is first in rank as far as sloping areas are concerned. Corresponding to a very large surface of Mediterranean land, these are especially sensitive areas, where soils are a qualitatively scarce resource. Sloping Mediterranean agri-environments heir a very significant part of cropping systems, crops and products traditional of the basin, vineyards and olive groves being the most relevant ones. Improvements in productivity and economic income of these areas are imperative to reduce population depletion and its impacts on territory sustainability. On the other hand, the long-term cultivated and highly eroded slopes ask for alternative land use models and management options that allow recovery of already much degraded environments. The importance of sloping areas, their land uses and misuses, comes also from their hydrological key role that, in the Mediterranean, has large consequences for water conservation, flood hazard and off-site effects of soil erosion. Soil protection initiatives are needed to cope with the threats to soil resource highlighted above. The thematic strategy for soil protection in Europe clearly sets the topic in high priority at policy level, as the need for soil protection is there stated in specific terms. This new political background encourages defining specifically oriented rationale in view soil protection measures design and implementation. Actually, expertise acquired in the last couple of decades throughout Europe, as part of the European strong research efforts in the topic, shows the high level of specialization necessary to tackle with soil protection issues. The still growing research-borne information has to be converted into technically useful tools for ―real world‖ problem solving. The thematic strategy for soil protection in Europe asks for such a challenge and problems posed on Mediterranean sloping areas are certainly important test-subjects. Foreword T. de Figueiredo & N. Evelpidou vi Figueiredo & Evelpidou As requirements stated in regulations eventually issued from the thematic strategy for soil protection in Europe become more specific, demand is expected to grow for technical staff able to deal with the design and implementation of soil protection measures. This is why and what for SPinSMEDE was designed, planned and organized. SPinSMEDE, acronym for Soil Protection in Sloping Mediterranean Agri- Environments, labels an Erasmus Intensive Programne that first took place in spring 2008, in Portugal, at Escola Superior Agrária of the Instituto Politécnico de Bragança. Intensive Programmes, within the Lifelong Learning Programme, are short duration higher education programmes, fully creditated within the ECTS framework. They stem on a transnational partnership of EU Universities, where students and professors come from, as in an Erasmus mobility scheme. For SPinSMEDE two-week and 6 credits Intensive Programme, the Polytechnic Institute of Bragança, the co-ordinating institution, promoted a partnership including the Wageningen University (The Netherlands), the National and Kapodistrian University of Athens (Greece), the University of Lleida (Spain), and the Unversity of Santiago de Compostela (Spain). The book objectives, target audience and general sequence of subjects, are all the same as those defined for the programme itself. Therefore, it is aimed at providing basic tools to assess soil degradation and to design soil protection initiatives in Mediterranean sloping areas. Rooted in both the EU thematic strategy for soil protection in Europe and the special environmental sensitivity of Mediterranean slopes, it is oriented towards the capacitation in such specific issue of post-graduation students, especially those with background in agricultural, forest or environmental engineering and those from life or earth sciences. The programme comprises two main parts, and this is reflected in the book contents. In order to allow a better insight on the Mediterranean environment, the texts of overview lectures addressed to geography and geology, climate, soils and vegetation are also presented. Background subjects, the first part, addresses soil degradation processes and assessment, soil protection measures design and implementation applying technical and socio-economic criteria. It is intended to provide the base knowledge necessary to better understand subjects treated in the second part. Selected case studies are presented and explored in the second part, and they concern land use typical of Mediterranean slopes, such as vineyards, olive groves, forests or shrubs. Not by chance, the book falls somewhere between the classical text book and the professionally oriented handbook. As so, after a more theorectically developed topic, the reader may find exercises that set the necessary links with ―real world‖ conditions and problems, and that guide in the application of methods to approach it. This book assembles the texts and reading material of most of the lectures and exercises given during the two editions of SPinSMEDE, the 2008, held in Bragança, and the 2009, held in Athens (a third edition is planned for spring 2010, in Santiago de Compostela). It is felt as a still in progress work, because the relevance of this thematic seemingly requires the attention of a wider audience than the one it may reach now, and, in turn, this goal asks for editorial refinements that, for the moment, could not be achieved according to expectations. Editors and contributors deeply wish their work to serve the outstanding and demanding cause of soil resource protection in the Mediterranean sloping agri-environments.